Turn It This Way: Remote Gesturing in Video-Mediated Communication - Kirk, David Stanley (2007)
Collaborative physical tasks are working tasks characterised by workers 'in-the-field' who manipulate task artefacts under the guidance of a remote expert. Examples of such interactions include paramedics requiring field-surgery consults from hospital surgeons, soldiers requiring support from distant bomb-disposal experts, technicians inspecting and repairing machinery under the guidance of a chief engineer or scientists examining artefacts with distributed colleagues. This thesis considers the design of technology to support such forms of distributed working. Early research in video-mediated communication (VMC) which sought to support such interactions presumed video links between remote spaces would improve collaboration. The results of these studies however, demonstrated that in such tasks audio-video links alone were unlikely to improve performance beyond that achievable by simpler audio-only links. In explanation of these observations a reading of studies of situated collaborative working practices suggests that to support distributed object-focussed interactions it is beneficial to not only provide visual access to remote spaces but also to present within the task-space the gestural actions of remote collaborators. Remote Gestural Simulacra are advanced video-mediated communication tools that enable remote collaborators to both see and observably point at and gesture around and towards shared task artefacts located at another site. Technologies developed to support such activities have been critiqued; their design often fractures the interaction between the collaborating parties, restricting access to aspects of communication which are commonly used in co-present situations to coordinate interaction and ground understanding.